Relationship between the severity of pre-frailty and the degree of adaptation of Ninjin’yoeito (NYT) on pre-frailty - Amitani, Haruka; Suzuki, Hajime; Kobayashi, Hironori; Murayama, Masaru; Uto, Nanami Sameshima; Kuroda, Eishi; Kobayashi, Yoshiki; Kawabe, Momoko; Amitani, Marie; Inui, Akio; Marunaka, Yoshinori (Frontiers in Aging, 2024)
With the global trend towards longer life expectancies, there's an increasing emphasis on not just living longer, but also maintaining health and well-being into older age. This study explores the efficacy of Ninjin'yoeito (NYT) in the early stages of frailty, a critical period for preventive interventions. Taking account of the knowledge gap regarding the association between early frailty and NYT, we use data from workplace health checkups to examine the relationship between pre-frailty severity and NYT adaption. The objective of our research is to enhance the comprehension of early treatments using NYT to prevent the progression of frailty.A total of 314 employees of the Kyoto Industrial Health Association who received workplace health checkups between November 2021 and March 2023 and consented to this study were included in the analysis. Information on gender, age, body mass index (BMI), NYT-specific symptoms assessment, the Japanese version of the General Health Questionnaire-12 (GHQ-12), and the Kihon Checklist (KCL) were obtained.The correlation analysis revealed that there was a strong positive correlation between the number of applicable NYT indications and the GHQ-12 score (r = 0.5992, p < 0.0001). Similarly, a moderate positive correlation was observed between the number of applicable NYT indications and the KCL score (r = 0.5030, p < 0.0001). In the multivariate analysis, both GHQ-12 (β = 0.49, SE = 0.06, t = 7.66, 95% CI: 0.36 to 0.62, p = 0.000) and KCL (β = 0.54, SE = 0.12, t = 4.29, 95% CI: 0.29 to 0.79, p = 0.000) showed significant positive associations with the variance in the number of applicable NYT indications, indicating that higher scores on these measures were related to a greater number of indications.NYT has the potential to be utilized not only as a therapeutic intervention for frailty, but also as a preventive measure.